The Psychometric Properties of the Norwegian version of Ravens Matrices (Standard Progressive Matrices (SPM)/Coloured Progressive Matrices (CPM)) - Helland-Riise, Fredrik; Martinussen, Monica (PsykTestBarn, 2017)
Description: There are different versions of Ravens Matrices including Coloured Progressive Matrices (CPM) (5–11 years) and Standard Progressive Matrices (SPM) (8–65 years) which may be used for children and adolescents. The test was first developed by John C. Raven, and the SPM was published in 1938, and the CPM in 1998. The test is assumed to measure non-verbal intelligence or abstract reasoning ability with items consisting of geometrical figures where the task is to figure out the system underlying the figures. Both versions of Raven have items with increasing difficulty organized in different sets. The test is scored in terms of the number of correct answers, which is summed to a total score. The total score can be converted to percentiles based on norm tables included in the manuals. The test is usually administered without time constraints for children and adolescents, and the test user is required to be a psychologist or a certified user of ability tests.Pearson Assessment holds the copyright to Ravens Matrices, and is responsible for sale and distribution of the test in Scandinavia and internationally (pearsonassessment.no). Literature search: A total of 15 Norwegian and 24 Swedish/Danish publications were included in the review. None of these were psychometric studies, but mainly studies where Raven had been used to measure intelligence either as an outcome variable, control variable or to describe the group. Approximately half of the included studies were based on clinical groups (e.g., autism, epilepsy or deaf), while the remaining studies included school children of 5–16 (SPM) and 5–7 (CPM) years. Psychometrics: None of the included studies had performed adequate studies of test reliability and there were no norm studies based on Norwegian or Swedish/Danish samples. The findings support the construct validity of the test as a good measure of abstract reasoning ability by in general high correlations with other cognitive tests. Conclusion: There is solid evidence supporting the construct validity of the test, but studies examining test reliability using Scandinavian samples are lacking. There are no norm studies from Scandinavia, which is problematic for clinical and applied test use.